PENGARUH PENGUNGKAPAN TANGGUNG JAWAB SOSIAL DAN TATA KELOLA PERUSAHAAN TERHADAP NILAI PERUSAHAAN (Studi Empiris pada Perusahaan Infrastruktur yang Terdaftar di Bursa Efek Indonesia pada Tahun 2021-2023) - Ryaas Mahardika Muhammad; Dul Muid (Diponegoro Journal of Accounting, 2026)
This study aims to determine the effect of corporate social responsibility (CSR) disclosure and corporate governance on firm value. In this study, corporate governance is proxied by two variables: the size of the board of commissioners and the proportion of independent commissioners. Meanwhile, the firm value variable is measured using the Tobin’s Q method. The research population consists of infrastructure sector companies listed on the Indonesia Stock Exchange (IDX) during the 2021–2023 period. Sample selection was conducted using the purposive sampling method, yielding a total of 75 observational data after excluding outliers. The data analysis method employed is multiple linear regression analysis, processed using SPSS software. The results of the hypothesis testing indicate that the corporate social responsibility disclosure variable has a negative and significant effect on firm value. The board of commissioners size variable has no significant effect on firm value. On the other hand, the proportion of independent commissioners variable is proven to have a positive and significant effect on firm value. The resulting Adjusted R Square value is 0.232, indicating that the capacity of the independent variables to explain firm value is 23.2%, while the remaining 76.8% is explained by other factors outside the research model.